Purification of Cd, Zn and Te for CdZnTe growth - Meier, Michael (Kansas State University, 2009)
Purification of cadmium, zinc and tellurium was attempted to improve the quality of cadmium-zinc-telluride (CdZnTe) crystal growth. Specifically, vacuum distillation, zone refining and H[subscript]2 gas flow assisted zone refining were all investigated as methods to purify the constituent elements of CdZnTe. A unique multi-chamber ampoule was used to enable a purification sequence starting with double vacuum distillation followed by zone refining all without sample handling after the initial step. Modifications due to unique material properties of Cd and Zn were developed. Glow discharge mass spectroscopy (GDMS) analysis was used to measure impurity concentrations of 74 elements. Cd purification using vacuum distillation proved to be an effective method to reduce the impurity level of 5N starting material to a purity between the range of 6N5 and 7N5, as measured using GDMS and laser ablation mass spectroscopy. Combined Zn double vacuum distillation and zone refining in an enclosed Ar atmosphere using 5N starting material yielded material with a purity between the range of 5N8 to 6N8. Tellurium purification using combined double vacuum distillation followed by zone refining under continuous H[subscript]2 flow of 4N specified raw material resulted in high purity tellurium between the range of 6N3 and 7N4.
Keywords: zone refining; purification; Cadmium; Zinc; Tellurium; distillation; Engineering, Materials Science (0794); Engineering, Metallurgy (0743); Engineering, Nuclear (0552)